When Ritual Meets the Feed: TikTok, Mediatization, and the Reconfiguration of Hindu Religious Authority - I Ketut Putu Suardana; Zohaib Hassan Sain (Khazanah Theologia, 2025)
Purpose: This study analyzes how a Hindu pandita’s transcendent communication (mantra recitation and ritual practice) is mediatized on TikTok by examining content characteristics, engagement dynamics, and audience negotiations between sacred values and platform logic. Methodology: Using a qualitative netnographic approach, the study focuses on the TikTok account @idapandita65. Data were collected through non-participant observation of 86 video posts and 2,144 user comments from January–April 2025, alongside recorded engagement metrics (likes, views, and comments). Findings: Three main findings emerged. First, extended rituals were recontextualized into short-form videos with an average duration of 3.2 minutes, and 67.4% of posts involved self-recording during mantra/ritual performance. Second, engagement increased sharply in April 2025 (20,322 likes; 509,204 views), representing 5,084% and 4,822% increases respectively compared to January, occurring in temporal proximity to the post-Nyepi period (Nyepi: 29 March 2025) and Galungan (23 April 2025), followed shortly by Kuningan (3 May 2025). Third, audience responses were polarized: 45% were appreciative (n=964), 38% were critical—particularly regarding sanctity, concentration, and sesana in self-recorded ritual content (n=814)—and 17% were humorous/ambivalent (n=366). Implications: Theoretically, the findings suggest that TikTok affordances and platform metrics do not merely transmit religion but actively reshape the logic of spiritual authority through algorithmic visibility and public participation. Practically, the study offers guidance for Hindu leaders and institutions to develop digital strategies that protect ritual integrity (e.g., considering delegated recording), and it highlights for platform designers and policymakers the sensitivity of contemplative and sacred ritual content in entertainment-oriented environments. Originality: This study extends mediatization theory to embodied and sonic Hindu ritual practices on short-video platforms, providing empirical evidence on audience polarization and demonstrating how production methods (self-recording vs. third-party recording) shape perceptions of authenticity and religious legitimacy.